Analytical formulation of relationship between ionization current and extracted ion beam current in a Penning ion source - Silakhuddin, Silakhuddin; Kudus, Idrus Abdul; Jati, Bambang Murdaka Eka; Palupi, Dwi Satya; Taufik, Taufik; Mulyani, Emy; Heranudin, Heranudin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
A study on the performance of the Penning-type internal ion source of the DECY-13 cyclotron has been conducted to evaluate the relationship between cathode current and extracted ion beam current, as well as the stability of the extracted beam. The DECY-13 cyclotron, developed at the Research Center of Accelerator Technology, BRIN, is designed to produce 13 MeV protons for radioisotope production. In the experiment, the cathode current was varied between 200-400 mA, while the magnetic field and extraction voltage at 1.25 T and 3 kV, respectively. The results indicate a clear power-law dependence between cathode current (Ic) and extracted beam current (Iext), expressed as Iext=343.8 Ic^1.42 . This relationship suggests that ionization efficiency increases sharply with cathode current. Stability tests at 400 mA cathode current showed that the extracted beam current remained stable at ~70 μA over 45 minutes, with only minor fluctuations. These findings demonstrate that cathode current is an effective parameter for controlling extracted beam current. The results contribute to a better understanding of ion source behavior in cyclotron systems and provide a foundation for further optimization of Penning ion sources for radioisotope production.